2021
DOI: 10.1140/epjd/s10053-021-00283-5
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma technology for removal of organic micropollutants from wastewater—a review

Abstract: Water bodies are being contaminated daily due to industrial, agricultural and domestic effluents. In the last decades, harmful organic micropollutants (OMPs) have been detected in surface and groundwater at low concentrations due to the discharge of untreated effluent in natural water bodies. As a consequence, aquatic life and public health are endangered. Unfortunately, traditional water treatment methods are ineffective in the degradation of most OMPs. In recent years, advanced oxidation processes (AOPs) tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 155 publications
0
10
0
Order By: Relevance
“…In PAW, other important formation mechanism of OH˙radical in the bulk liquid is through the degradation of peroxinitrous acid (O=NOOH)-formed by the reaction between H 2 O 2 and NO 2 − -in acidic conditions [13]. Pollutant degradation (such as pharmaceuticals, pesticides and organic dyes) in water induced by nonthermal plasma discharges in (and in contact with) liquids has been extensively studied, as summarized in a recent review articles [15,18]. The principal mech-anism of pollutant degradation is associated with the most reactive species (OH˙, O 2 ˙−, O 3 ) formed in the gas phase during the discharge, which enter in the liquid bulk, react with the contaminant molecule, and fragment it.…”
Section: Introductionmentioning
confidence: 99%
“…In PAW, other important formation mechanism of OH˙radical in the bulk liquid is through the degradation of peroxinitrous acid (O=NOOH)-formed by the reaction between H 2 O 2 and NO 2 − -in acidic conditions [13]. Pollutant degradation (such as pharmaceuticals, pesticides and organic dyes) in water induced by nonthermal plasma discharges in (and in contact with) liquids has been extensively studied, as summarized in a recent review articles [15,18]. The principal mech-anism of pollutant degradation is associated with the most reactive species (OH˙, O 2 ˙−, O 3 ) formed in the gas phase during the discharge, which enter in the liquid bulk, react with the contaminant molecule, and fragment it.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [27][28][29] have shown that plasma treatment is highly effective in the destruction of bacteria, pesticides [30], pharmaceuticals [31,32], organic dyes [33], and PFAS [34,35].…”
Section: Plasma Treatmentmentioning
confidence: 99%
“…Catalytic reactions offer promising solutions for the efficient and selective reduction of these pollutants, leading to their detoxification and elimination from water supplies. Regarding the state of the art in water decontamination, various technologies have been investigated, including activated carbon filtration, microbial remediation, chemical precipitation, membrane filtration, UV/ozone treatment, photocatalysis, Fenton processes, and catalytic reduction. In the development of such technologies, including catalytic reactions, efforts are underway to establish effective, safer, and more environmentally friendly decontamination methods.…”
Section: Introductionmentioning
confidence: 99%